(untitled) (CAHIERS MAGELLANES-NS, 2024)
‘Predatory pricing is taken to be a manifestation or sign of market dominance. But too often it is a precursor.’ According to the principles of economics, the demand for a commodity in a well-functioning market is determined by the price that consumers are willing to pay. This price reflects their perception of the commodity's value. In such a market, the supply of the commodity is determined by the amount of money spent on producing it. All market participants utilize the same manufacturing technique, and even if there are little variations, none of them possess enough strength to impact economies of scale or bring about a substantial alteration in the established fixed price. The Competition Act of 2002 considers situations where the supply of a commodity is mostly limited to a single market participant who, due to their dominant position, has become very powerful. This is because they have achieved low production costs, significant economies of scale, and advanced research and development capabilities that surpass many others. Predatory pricing may initially benefit consumers, but in the long term, they will bear the negative consequences. Nevertheless, authorities exercise caution over such techniques, as there is a high likelihood that the dominant player will eliminate competitors. Once the competition is undermined, prices will inevitably rise, leaving consumers with no choice but to accept the higher prices. This study aims to analyze the Indian competition legislation pertaining to predatory pricing and examine it in the context of abuse of dominance. This paper will analyze current charges of unfair competition against OLA and provide recommendations on how to address them.